Baclofen - a great chance or danger - discussion of poisoning based on research - Świątek, Gabriela; Tkaczyk, Rafał; Radoniewicz–Tchórz, Anna; Sosnowska, Weronika; Brzozowska, Aleksandra; Tomkiewicz, Maria; Tomczyk, Jakub; Tomkiewicz, Maciej; Trusz, Kornelia; Wanat, Iwona (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Baclofen is a derivative of γ-aminobutyric acid (GABA). It is a spasmolytic drug that reduces skeletal muscle tension and is used in spasticity. Despite its many positive functions, its use is associated with a risk of side effects. The aim of this work is to gain a better understanding of baclofen and to highlight the toxicity and dangers of its misuse. Material and methods: The study was retrospective in nature. It used an analysis of the records of 11648 intoxications in patients hospitalised from 01.04.2013 to 01.04.2023 in the Clinical Toxicology and Cardiology Department of the Stefan Cardinal Wyszyński Provincial Hospital in Lublin, from which a group of baclofen intoxicated patients (T55), consisting of 19 cases, was distinguished. Results: The study population consisted of 10 women (52.63%) and 9 men (47.37%), aged between 16 and 83 years. The largest group consisted of patients aged up to 30 years - 9 patients (47.37%). The majority of patients - 11 patients (59.89%) were in a severe condition. An overwhelming number reported intentional poisoning - 16 cases (84.21%), including five suicide attempts (31.25%). Patients took other drugs and medicines in addition to baclofen. The most common was ethanol - 8 people (42.11%), followed by NSAIDs - 5 people (26.32%). Conclusions: In order to prevent complications following the use of baclofen, it is very important to educate patients, their family members and the general public about the mechanism of action of the drug itself, its function on the body and the risks of taking it. Prophylactic measures and education on how to deal with poisoning situations are necessary, as they are entirely preventable with immediate diagnosis and treatment.